GROWTH AND BIOMETRIC RELATIONSHIP OF PEARL OYSTER PINCTADA FUCATA (GOULD) - Chellam, A (Indian Journal of Fisheries, 2011)
Observations on the growth of pearl oyster, Pinctadafucata (= P. vulgaris) of the Gulf of Mannar have been made b&sed on the spatfall (Herdman, 1903; Devanesen and Chidambaram, 1956; Chacko, 1970) and the initial size of transplantation to the farm (Chellam, 1978). Alagaraja (1962) has found out the lengthweight relationship of the pearl oysters cultured at the Krusadai farm by Devanesan and Chidambaram (1956) in cages.